A note on monetary policy and long-term interest rates in India: An efficient markets approach - Debaditya Mohanti; Souvik Banerjee (Journal of Applied Economics, 2024)
The present study aims to empirically analyze the relationship between the growth in money supply and the long-term interest rates in India through the application of efficient market theory. The study uses quarterly data over a period from 2010 to 2023. The advantage of the efficient market approach is that it provides a theoretical structure for explaining the relationship between the money stock and long-term rates. From the evidence, it can be suggested that there is no strong evidence for the view that growth in money supply is negatively correlated with changes in long-term interest rates. The implications of the study depend on the treatment of money supply processes in terms of exogeneity. If the growth in money supply is assumed to be exogenous, then the result of the present study opposes the commonly held view that an increase in the money supply would decrease the long-term interest rate.
Keywords: 330; efficient market theory; long-term interest rates; Monetary policy; money supply